Who killed higher education? : maintaining white dominance in a desegregation era - Chun, Edna Breinig (Routledge, 2022)
"Who Killed Higher Education?: Maintaining White Dominance in a Desegregation Era offers a probing and unvarnished look at the causes of the progressive state defunding of public higher education over the last seven decades. With the pandemic and cuts to social services, these challenges have only deepened, creating real dilemmas for first-generation, minoritized students seeking to complete a college education. Through extensive analysis of trends in public higher education funding, the book documents and lays bare the ways in which elite neoliberal decision-makers launched a multi-pronged and attack on public higher education. It highlights the confluence of the enrollment of an increasingly diverse cohort of students in college with the efforts of conservative white legislatures to diminish funding support for public higher education. Who Killed Higher Education? is an important resource for students in courses on higher education, and diversity in education. It will also provide instruction for boards of trustees, institutional leaders, faculty and key campus constituencies in developing long-term strategies that ensure the access and success of a diverse and talented student body"--